PENGARUH MODEL PROJECT BASED LEARNING TERHADAP KARAKTER KERJA SAMA SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR: Pengaruh Model Project Based Learning Terhadap Karakter Kerja Sama Siswa Pada Mata Pelajaran IPAS Di SD - Khairina Safitri; Hendri Marhadi; Guslinda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the effect of the Project Based Learning learning model on the character of cooperation of fourth grade elementary school students. The method used in this study is a quasi-experimental method with a nonequivalent control group design. The subjects in this study were fourth grade students of SD Negeri 39 Pekanbaru. The sample of this study was two classes, namely class IVA and IVB, where class IVA was used as the experimental class and class IVB as the control class. The researcher used the Project Based Learning learning model in the experimental class and the conventional model in the control class. The statistical data obtained were normality, homogeneity, and hypothesis tests, N Gain tests processed using the SPSS program. The results of the N-gain test showed that the experimental class had an average of 0.561 (moderate), while the control class was only 0.226 (low). In addition, the results of the hypothesis test using the independent T-test showed a significance value of 0.001 <0.05, so Ha was accepted and Ho was rejected. The posttest results showed that student cooperation in the experimental class was higher (86.34% - very high category) compared to the control class (75.13% - high category). This finding indicates that there is an influence of the use of the Project Based Learning learning model on the character of student cooperation in grade IV of SD Negeri 39 Pekanbaru.